The Zippity Zinger - Winkler, Henry, 1945- (Winkler, Henry, 1945- Hank Zipzer ;, 2004)
The pressure is on when Hank Zipzer is chosen as pitcher for the softball team at Public School 87's annual Olympiad, the most anticipated day of the school year.